PENYULUHAN CEGAH STUNTING PADA ANAK DALAM PERSPEKTIF SOSIAL BUDAYA DI KELURAHAN PONDAMBEA KOTA KENDARI - ashmarita ashmarita; Wa Ode Sitti Hafsah Wa Ode Sitti Hafsah; Abdul Jalil Abdul Jalil; Marsia Sumule Genggong; Ashmaria Ashmaria; Adinda Putri Pangerang (UNIVERSITAS KHAIRUN, 2023)
Children or infants under five years who are below the standard height or shorter than children their age are referred to as stunting. Stunting is caused by inadequate nutritional intake for a long time, resulting in impaired physical growth in children. In general, the province of Southeast Sulawesi has a stunting prevalence of 31.4%, while the city of Kendari is 28.6%7. These figures are still above the target of the World Health Organization (WHO), which is below 20%. The high rate of stunting is generally caused by limited knowledge of nutrition and a healthy lifestyle. Various unhealthy eating cultures are still developing and practiced by certain ethnic groups in society. Improving a healthy lifestyle and preventing stunting through a socio-cultural approach is a very important issue. This paper is the result of community service related to efforts to prevent stunting in children through a socio-cultural approach. This service is performed through counseling in Kelurahan Pondambea, Kendari City. The counseling was carried out together with partners from the puskesmas Merkar, Kendari City. The results of this service show that knowledge about healthy lifestyles for some people is still limited. The unhealthy eating culture is still practiced in several ethnic groups living in Kelurahan Pondambea, Kendari City. Therefore, a socio-cultural approach is still needed to provide education to the community.